Determinants of Foreign Direct Investment in Vietnam in the Context of Global Integration - Ngo, Duong Minh (Acta Carolus Robertus, 2024)
This study is conducted to find out the determinants of Foreign Direct Investment in Vietnam, especially focusing on the roles of economic growth, financial stability, trade openness, debt, inflation, and impacts of FTAs. We apply a multiple linear regression model and analyze these enablers’ impacts on FDI inflows. Further, we try to analyze the impacts that Vietnam’s becoming a part of the WTO and different FTAs has, in particular: ASEAN Free Trade Area (AFTA), Vietnam-Japan Economic Partnership Agreement (VJEPA), Vietnam-Korea Free Trade Agreement (VKFTA), and the EU-Vietnam Free Trade Agreement (EVFTA), by using them as the dummies in our model. Moreover, the study outlines the comparison of models with and without the dummy variables in order to have a clearly look at global integration when it comes to attracting FDI. Each dummy variable is also considered both simultaneously and separately, so as to clarify its role. The results highlight that lagged FDI, infrastructure, and natural resources are significant positive factors for FDI, whereas inflation has a negative impact. Trade openness and market size, however, do not show consistent significance. The WTO’s significance, particularly in models with FTAs, underscores the importance of global trade norms and reduced trade barriers in attracting FDI.